2010
DOI: 10.1111/j.1471-6712.2009.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Grief responses and coping strategies among infertile women after failed in vitro fertilization treatment

Abstract: Reproductive technology has increased the childbearing potential for many infertile women, but in vitro fertilization (IVF) failures are common, which often trigger grief responses and coping strategies to manage the stressful life event. The present cross-sectional study investigated 66 women who had experienced at least one failure with IVF treatment. The data were gathered by a self-administered structured questionnaire, and included the participant's personal profile, grief responses and the Jalowiec's cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
4
24
0
5
Order By: Relevance
“…Women who passed these stages but experienced a failure in treatment stated that they felt insufficient, empty, an absence, guilty, sad, like a failure, and deep sorrow. [29][30][31] In this study, these factors effectively promoted a high level of…”
mentioning
confidence: 75%
“…Women who passed these stages but experienced a failure in treatment stated that they felt insufficient, empty, an absence, guilty, sad, like a failure, and deep sorrow. [29][30][31] In this study, these factors effectively promoted a high level of…”
mentioning
confidence: 75%
“…For this reason, they claimed that the care given to women whose infertility treatment results in failure should be continued. 31 Lancastle and Boivin stated that the attempts to cope in the process of waiting for the pregnancy test result allowed women to pass this duration of waiting more positively and in a relaxed manner. 32 Related studies revealed that use of effective coping methods in the infertility treatment process helped decrease the influence of infertility and the level of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [16] evaluated psychological adjustment toIVF and found that overall women adjusted well to unsuccessful treatment cycles, as have some other studies which have concluded no change or positive emotional adjustment following failure [1718]. In spite of this, numerous studies have found that women and men experience negative psychological outcomes after unsuccessful treatment [1928]. With an increasing number of couples seeking treatment, including older couples, it is important to assess potential psychological impacts associated with failed treatment and to have this evidence incorporated in health policy deliberations on funding, access, and eligibility.…”
Section: Introductionmentioning
confidence: 99%